2009
DOI: 10.1111/j.1365-2621.2009.02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of enzyme to improve the technological quality of a panettone like baked product

Abstract: The aim of this work was to study the influence of amylase, xylanase and lypase on quality parameters of panettone. Two concentrations of each enzyme were utilised. Besides, enzymes were added to dough or to sponge in order to analyse the effect of the time at which the enzymes were added on bread quality. Results showed that enzymes improved the quality of the product. Depending on the enzyme, the effect was more remarkable on bread height, cell distribution or crumb texture. Particularly, lipase and amylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Low values of elasticity and high chewiness are usually indicators of storage time [ 31 ]. Lower moisture is related to aged and dry bakery products that require more salivation and chewing, although chewiness is directly related to the presence of fat and sugar [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low values of elasticity and high chewiness are usually indicators of storage time [ 31 ]. Lower moisture is related to aged and dry bakery products that require more salivation and chewing, although chewiness is directly related to the presence of fat and sugar [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quality of panettone is defined by its physical and chemical properties (moisture, color, specific volume, density and texture), which influence consumer acceptability [ 6 ]. To improve the fermentation process, enzymes (amylase, xylanase and lipase) are used to influence the quality of the product [ 7 ]. The fermentation process is important because it influences the sensory attributes of the product, as well as the recovery of the yeast and lactic acid bacteria that are involved in sourdough fermentation and produce the desired aromas and/or aromatic precursors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here overall sensoric evaluation indicated better fl avor, taste, softness and overall acceptability. A study by Benejam et al (2009) showed that amylase, xylanase and lipase improve the quality with regard to height, cell distribution and crumb texture in panettone. Results were dependent on whether the enzymes were added into the sponge or the dough.…”
Section: Unproved Frozen Doughmentioning
confidence: 98%
“…Various additives are used to improve the dough properties and bread quality in the bakery industry (Benejam, Steffolani, & León, 2009) and currently enzymes play an important role in baking technology (Shah, Shah, & Madamwar, 2006). It has been shown that the application of enzymes or emulsifiers or a mixture of both, can significantly improve the quality of bread elaborated with whole wheat flour (Grausgruber, Miesenberger, Schoenlechner, & Vollmann, 2008).…”
Section: Introductionmentioning
confidence: 98%